2022
DOI: 10.1093/jac/dkac304
|View full text |Cite
|
Sign up to set email alerts
|

Trimethoprim/sulfamethoxazole pharmacodynamics against Stenotrophomonas maltophilia in the in vitro chemostat model

Abstract: Background Trimethoprim/sulfamethoxazole has historically been the treatment of choice for infection caused by Stenotrophomonas maltophilia. This study sought to define the pharmacodynamic indices and magnitude of exposure required for stasis and 1 log10 cfu reductions. Methods Pharmacodynamic studies were conducted using the in vitro chemostat model over 24 h against three trimethoprim/sulfamethoxazole-susceptible S. maltoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…According to the PK/PD breakpoint, cotrimoxazole should not be recommended to treat an infection due to isolates with MICs higher than 0.5 mg/L since drug exposure is insufficient. These results agree with Lasko et al [ 18 ], who demonstrated that cotrimoxazole in monotherapy even at a high dose displays limited activity against cotrimoxazole-susceptible S. maltophilia strains. In fact, several authors have pointed out the necessity of redefining the breakpoints of cotrimoxazole for S. maltophilia [ 8 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…According to the PK/PD breakpoint, cotrimoxazole should not be recommended to treat an infection due to isolates with MICs higher than 0.5 mg/L since drug exposure is insufficient. These results agree with Lasko et al [ 18 ], who demonstrated that cotrimoxazole in monotherapy even at a high dose displays limited activity against cotrimoxazole-susceptible S. maltophilia strains. In fact, several authors have pointed out the necessity of redefining the breakpoints of cotrimoxazole for S. maltophilia [ 8 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…A reduction in bacterial cell count was not observed for any S. maltophilia isolate while susceptible E. coli isolates experienced killing at all MIC values. The group also examined the same TMP‐SMX simulated dose in a chemostat model 49 . TMP‐SMX exhibited limited activity with only two experiments demonstrating a ≥ 1‐log 10 CFU/mL reduction.…”
Section: Methodsmentioning
confidence: 99%
“…The group also examined the same TMP-SMX simulated dose in a chemostat model. 49 TMP-SMX exhibited limited activity with only two experiments demonstrating a ≥ 1-log 10 CFU/mL reduction. These results corroborate previous evidence in which simulated doses up to 15 mg/kg (TMP component) q12h did not reduce bacterial cell counts of four susceptible S. maltophilia isolates in a one-compartment model.…”
Section: Trimethoprim-sulfamethoxazolementioning
confidence: 96%
“…Time-kill analysis demonstrated that exposure of SXT-susceptible Sma isolates to 4/40 μg/ml for 24 h, which approximates the free steady-state concentration of a daily dose of 20 mg/kg of TMP, does not achieve colony forming unit (CFU) reduction [90 ▪▪ ]. Likewise, in an in vitro chemostat model, SXT stasis was achieved at a ratio of the area under the unbound drug time curve over 24 h to the MIC (fAUC/MIC) of 67.4 and 30 for TMP and sulfamethoxazole, respectively; however, clinically meaningful exposures required to achieve 1 log 10 CFU/ml reductions were not quantifiable [91 ▪▪ ]. The toxicity profile of high doses of SXT, which includes nausea/vomiting, hyperkalemia, fluid overload, and possible nephrotoxicity, is another issue that needs to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Average susceptibility rates for this agent varies among geographical regions, being the highest in Europe (>95%), followed by the Middle East (≈93%), USA (≈90%), Latin America (≈80%), and the lowest in Asia (<80% in China; 87% in Korea) [17,31 ▪ ,34 ▪ ,42,83 ▪▪ ,84 ▪ –88 ▪ ]. SXT lacks established PK/PD index or target threshold for efficacy or toxicity, which severely impairs the ability to optimize its clinical use [34 ▪ ,89 ▪ ,90 ▪▪ ,91 ▪▪ ,92]. In fact, data supporting guidance-recommended dosing of 8–12 mg/kg/day [trimethoprim (TMP) component] is sparse [93].…”
Section: Introductionmentioning
confidence: 99%